Performance test of different silicon photomultipliers for the 6LiF:ZnS(Ag) based neutron detectors of CSNS. (1st December 2022) - Huang, C.; Tang, B.; Yu, Q.; Yao, Z.; Sun, Z.J.; Tang, M.J.; Jiang, J.J.; Cai, X.J.; Yue, X.P.; Zhou, S.H.; Chen, S.J.; Wang, X.K.; et al.
Abstract: The China Spallation Neutron Source (CSNS) is a large scientific facility whose main aim is to support multidisciplinary research on material characterization using neutron scattering. Twenty neutron spectrometers will be built as multidisciplinary platforms for scientific research by national institutions, universities, and industry. Scintillator neutron detectors for the spectrometers under construction have recently been developed using silicon photomultipliers (SiPMs) for the readout. This paper studies the characteristics of three candidate SiPMs, including the breakdown voltage, gain, temperature coefficient, dark count rate, and radiation tolerance. Two measurement platforms were built to evaluate each SiPM. We summarize the results from our analysis of laboratory tests and beam test data to characterize the performance of the SiPMs. The MicroFJ-30035-TSV SiPM manufactured by the SensL Corporation is chosen as the best SiPM for the scintillator detectors at CSNS.